'When my mummy and daddy aren't looking at me when I do my maths she helps me'; Children can be taught to create imaginary companions: An exploratory study. Issue 2 (13th December 2022) - Davis, Paige E.; King, Nigel; Meins, Elizabeth; Fernyhough, Charles
Abstract: Spontaneous imaginary companion (SIC) creation in childhood is a typical imaginative play behaviour associated with advanced sociocognitive skills; however, the direction of causality has not been established. To investigate this experimentally, researchers must determine whether children can create, on request, qualitatively equivalent imaginary companions (ICs) to those created spontaneously. We examined whether children could create ICs, and how these compared to SICs. Nine elementary school children were encouraged to create ICs in a 3‐month intervention. Accounts of elicited ICs were compared with an age‐matched sample of interviewees with SICs. Seven children maintained ICs for 6 months post intervention. Template analysis of IC interviews found four themes: Realistic Play, Multifaceted IC Mind, Utility of the IC, and Elicited IC Across Time. Analysis suggests elicited and SICs were similar in nature and utility, although intervention ICs tended to have animal rather than human appearances. Findings support the argument that children can be encouraged to create ICs similar to SICs.